Kajian Transformasi Perusahaan: Studi Pada PT Telekomunikasi Indonesia, Tbk. - , Dani Krishnamulya Ristandi ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The purpose of this study is to examine the transformation program being implemented by PT Telekomunikasi Indonesia, Tbk. (Telkom), and to see further about force of changes as basis of this program, also to observe how Telkom run this program as well as the results in the period 2008-2011. This research used descriptive research methods to the type of case study. The data used are secondary data as the main data coupled with primary data as additional data supplemented. Besides, the extensive literatures to support these findings and to determine the exact framework of the work in implementing change management in particular about the transformation. The secondary and primary data as well as literature studies indicate that factors external factor of force of changes become as important and dominant factors for Telkom to decide to do the transformation. Furthermore Telkom transformation is a transformational change because in addition involves the processes, systems, people and culture. In terms of achievement, this transformation showed good results with an indication of a new wave of business growth is increasingly significant as compared to legacy business. The research has limitations that can not be avoided that term transformation program that has been running for 4 years from 2008 to 2011. To overcome these limitations, the authors limit the company's response efforts in the face of conditions they experienced and saw the changes done during the transformation.